The Behavior of Dissolved Gas in Difference Liquid Insulation With ZnO Under Thermal Ageing Condition - Korraya Jongvilaikasem; Chanin Bunlaksananusorn; Wanwilai Vittayakorn; Norasage Pattanadech (My University, 2024)
Mineral oil is a commercial product that has been widely used as a dielectric liquid in transformers. However, alternative liquids have been developed to gradually replace mineral oil because of some better liquid insulating properties in the point of safety aspect and environmentally friendly. This paper represented the behavior of Dissolved Gas in different types of liquid insulations mixed with nanoparticles under thermal aging conditions. Various types of liquid insulation including mineral oil, natural ester, and palm oil added with a 0.03% concentration of zinc oxide (ZnO) and sorbitan mono-oleate surfactant (Span 80) underwent thermal stress aging at 90, 110, 130, and 150 degrees Celsius with 200 mbar for 72 hours in a vacuum oven. Then, the concentration of dissolved gas in the stressed samples was investigated by the Dissolved Gas Analysis (DGA) technique. From the test results, it was discovered that distinct liquid insulations and aging temperatures produced diverse dissolved gas generation behaviors. Besides, the dielectric liquid with Nanofluids or Nanofluids mixed with span 80 seems to have no different dissolved gas generation behaviors.
Keywords: Aerogels and thermal insulation; High voltage insulation and dielectric phenomena